Boosting the performance of poly(ethylene oxide)‐based solid polymer electrolytes by blending with poly(vinylidene fluoride‐co‐hexafluoropropylene) for solid‐state lithium‐ion batteries. (23rd April 2020) - Li, Jialun; Zhu, Lin; Xu, Jianing; Jing, Maoxiang; Yao, Shanshan; Shen, Xiangqian; Li, Songjun; Tu, Feiyue
Summary: To seek a solid polymer electrolyte (SPE) with excellent performance, a novel poly(ethylene oxide) (PEO) based SPE is prepared by blending an appropriate amount of microcrystalline poly(vinylidene fluoride‐ co ‐hexafluoropropylene) (PVDF‐HFP) with PEO using a universal solution casting method. Field emission scanning electron microscopy (FESEM), X‐ray diffraction (XRD) and differential scanning calorimetry (DSC) are utilized to analyse the samples. The crystallinity of the blend solid polymer electrolyte is significantly lower than that of the neat PEO‐based SPE. The addition of the PVDF‐HFP disrupts the segment structure of the PEO crystal region and increases the proportion of the amorphous region, thus boosting the migration of lithium ions. The results show that the electrochemical stability window of the blend solid polymer electrolyte reaches as high as 4.8 V. The initial discharge specific capacity of the solid‐state LiFePO4 /SPE/Li battery is 131 mAh g −1 at 0.5 C and 60°C, and the discharge specific capacity is still 110.5 mAh g −1 after 100 cycles. On the basis of the results, the novel SPE has a widespread application prospects in solid‐state lithium‐ion batteries.